Quality of life indicators in assessing the results of various surgical treatment methods for cervical myelopathy - A. A. Chekhonatsky; N. E. Komleva; V. N. Nikolenko; V. A. Chekhonatsky (Неврология, нейропсихиатрия, психосоматика)
Quality of life indicators are widely used to determine the efficiency of various medical therapies for cervical myelopathy; however, but these have been insufficiently studied in assessing the results of surgical treatment for this pathology. In addition, the results of surgical treatment for cervical myelopathy are observed to be unsatisfactory in 15–20% of cases, which indicates the need to develop new techniques and to improve existing ones for its correction. Direct electrical stimulation of the spinal cord may become one of the promising areas.Objective: to comparatively analyze the efficiency of various surgical treatments for cervical myelopathy, by assessing the quality of life indicators in the patients.Patients and methods. The investigation enrolled 92 patients with cervical myelopathy: 29 (49.2%) patients underwent posterior spinal cord decompression via laminectomy; in 17 of them, that was supplemented with the electrodes placed on the posterior columns of the spinal cord for its postoperative direct electrical stimulation; 63 (50.8%) patients underwent anterior spinal cord decompression, 12 of them had electrodes placed on the anterior horns of the spinal cord.Results and discussion. After posterior spinal cord decompression with laminectomy, there were increases in physical functioning from 36.7±2.1 to 49.6±3.1 arbitrary units (arb. unit) (p<0.05) and in role physical functioning from 39.4±2.6 to 51.3±2.6 arb. unit (p<0.05) and a decrease in pain sensations from 51.6±2.6 to 30.2±0.8 arb. unit (p<0.05). Electric stimulation of the spinal cord caused increases in physical functioning from 40.3±3.6 to 61.3±2.8 arb. unit (p<0.05) and in role physical functioning from 36.7±1.6 to 69.4±1.6 arb. unit (p<0.05) and a reduction in pain sensations from 49.8±2.4 to 21.0±1.2 arb. unit (p<0.05). The similar trend as also observed in anterior spinal cord decompression concurrent with corporodesis at the cervical level after direct electrical stimulation of the spinal cord. Physical functioning increased from 42.0±3.1 to 57.6±1.4 arb. unit (by 26.4%; p<0.05) and mental health improved (only by 14.3%). After isolated anterior spinal cord decompression with corporodesis, physical functioning was 48.4±0.9 arb. unit by the end of the third month follow-up (p<0.05); following that in combination with electrical stimulation, physical functioning was 57.6±1.4 arb. unit (p<0.05). The posttreatment levels of viability, social functioning, role emotional functioning, and mental health were significantly lower in patients with a disease duration of more than 6 years than in those with that of less than 3 years.Conclusion. Posterior and anterior spinal cord decompression with laminectomy for cervical myelopathy increases the indicators of physical functioning and role physical functioning and reduces pain sensations. The additional use of electrical stimulation of the spinal cord allows one to increase role physical functioning.